Ultrasound-Assisted Extraction of Antioxidant Compounds from “Cẩm” Purple Rice Bran for Modulation of Starch Digestion - Le Thi Kim Loan; Nguyen Minh Thuy; Ngo Van Tai (International Journal of Food Science)
Purple rice, locally known as “Cẩm” rice, is cultivated in the southern region of Vietnam. The bran of “Cẩm” rice is often disregarded and underutilized; nevertheless, it harbours substantial nutritive value, particularly in terms of antioxidant compounds. Additionally, sonication, an emerging and “green” technological approach, has been employed to augment the extraction efficiency of these antioxidants. This research is aimed at optimizing and maximizing the antioxidant recovery capacity including phenolic and total flavonoid compounds, along with their antioxidant activities, through the assistance of ultrasound waves. The effect of the extract on the starch digestion process was also investigated. The study employed the Box-Behnken experimental design, encompassing three variables: extraction time (20-40 minutes), temperature (60-80°C), and solvent-to-material ratio (8 : 1 to 12 : 1). Analysis was conducted on total phenolic compounds, total flavonoid content, and antioxidant activities. Results demonstrated that the peak yield of antioxidant compounds and their corresponding activities were attained at an extraction duration of 29.38 minutes, a temperature of 69°C, and a solvent-to-material ratio of 9.92. Under these optimal conditions, the yields were as follows: total phenolic compounds at 60.821 mg GAE/g, total flavonoid compounds at 3.2696 mg QE/g, percentage inhibition of DPPH at 74.778%, and FRAP value at 54.112 μmol Fe (II)/g. The established models were validated and exhibited a strong alignment between predicted and actual values, with disparities of less than 3% under optimal conditions. Furthermore, the extract was codigested with cooked corn starch, revealing a dose-dependent effect on starch digestibility. The sluggishness of digestion rate was observed when 20 mg of the extract was supplemented to 200 mg of cooked corn starch. This suggests that rice bran extract holds promise as an effective ingredient for mitigating starch digestion, particularly beneficial for individuals dealing with diabetes.